Case Report: Use of PET/CT to Guide Treatment in a Cat With Presentation Consistent With Hodgkin's-Like Lymphoma - Chen, Carolyn L.; Cook, Matthew R.; Brown, Megan E.; Lumbrezer-Johnson, Sarah; Hostnik, Eric T.; Lapsley, Janis M.; Lerche, Phillip; Wavreille, Vincent A.; Menendez, Maria I.; Knopp, Michael V.; Linn, Sarah C.; Premanandan, Christopher; et al. (Frontiers in Veterinary Science, 2021)
An 8-year-old male neutered Domestic Long Hair cat was presented for a cervical swelling that was suspected to be an enlarged left retropharyngeal lymph node. In the absence of other lymphadenopathy, this was initially suspected to be Hodgkin’s-like lymphoma. A positron emission tomography-computed tomography (PET/CT) scan was performed using 2-deoxy-2-[18F]-fluorodeoxyglucose (18F-FDG) to assess for evidence of disease in other locations to guide treatment. Multifocal increased radiopharmaceutical uptake was identified, indicating disease in multiple organs. High grade lymphoma was confirmed on tissue biopsy. As such, systemic cytotoxic chemotherapy was recommended instead of lymph node extirpation surgery. The cat received a modified CHOP chemotherapy protocol and attained a temporary partial remission. After 2 months of treatment, the cat stopped responding to chemotherapy and was eventually euthanized due to a relapse of disease and decreased quality of life. This case describes the utility of PET/CT to guide treatment in a cat with a presentation consistent with Hodgkin’s-like lymphoma.